Mejora en la disposición de planta de la empresa Ingeniería, Fabricación y Montaje S.A.C. - Campana Chavez, Jimena Carolina (2017)
The present research seeks to find an improvement that optimizes the production process through a proper relocation of work areas and equipment, and thus facilitate efficient performance and increase the productivity of the company. In Chapter I, a current description of the company is made, with a brief historical review of it and also referring to the products they offer. In addition, as an important part of the research, the objectives, the technical, economic and social justifications, the work hypothesis and the reference framework that served as support for the research are presented. In Chapter II, an analysis of the competitive forces and external forces is developed, as well as a description of the main product process the company offers, in this case the dryer. In addition, the main management indicators are shown. In Chapter III, a general diagnosis of the company was made. A matrix of problem selection was used, which was developed with the general manager. From there, the main problem that was found in the area of production and Is the inadequate plant layout, and thus using the Ishikawa method, the root causes of the problem were determined, which are hierarchized by means of the Pareto Diagram. Chapter IV proposes alternatives to solve the problems identified in the previous chapter, where the best solutions were selected through a factor ranking. In Chapter V, the procedures for each solution selected in the previous chapter are described in detail, and most of the engineering tools related to the topic are used. The general budget required for the execution of the solution is presented. In addition, a schedule is detailed in a Gantt Diagram the tasks to be performed step by step in order to comply with the entire implementation of the improvements. Chapter VI identified potential scenarios for planned improvements and a financial economic evaluation of the solution is made. In addition, the social and environmental impacts that bring about the improvements of the company are presented.